Factors Effecting Intention to Leave at Fajar Surya - Lukmansyah Rifai Amirudin Rifai Amirudin; Madhakomala; Wibowo (Fakultas Ekonomi, Universitas Negeri Jakarta, Indonesia, 2022)
Turnover is a level of employee exit in a company. This research aims to develop an impact strategy model of job insecurity, career development opportunity, work involvement and work engagement on turnover intention. Quantitative methods are used ini this research. The sample consists of 150 employees with a managerial level. The sample criteria in this research are permanent employees and have worked for at least 3 years. Data collection techniques by distribution questionnaires directly to all samples. The data analysis used is SEM-PLS (Structural Equation Modeling - Partial Least Square). The results showed that job insecurity, career development opportunity and work engagement have significant influence on turnover intention. Career development opportunity and work engagement have negative and significant impact on turnover intention, while job insecurity has negative and significant impact on turnover intention. Job insecurity and career development opportunity mediated by work engagement have significant influence on turnover intention. Meanwhile, work engagement as mediating variable has no significant impact on turnover intention.